2013
DOI: 10.14260/jemds/355
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Atrophic Rhinitis

Abstract: To evaluate the clinical feature & pathology of atrophic rhinitis [AR] 75 cases of AR were evaluated retrospectively. Maximum cases were in the age group 20-30 years [40%].Male: female ratio was 1:1.5. Major symptoms were foul smell from nasal cavity along with crusting. The major signs found were atrophy of lateral nasal wall along with turbinates & nasal crusting. The most common organism found in nasal cavity & antrum were Pseudomonas aeruginosa followed by Klebsiella ozaenae. The present study describes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…28 In a study by Mishra et al, maximum number of cases was in the age group 21-30 years (40%). 27 The present observations also correlate with the study of Shreedharan et al, and Jain et al 29,30 In the present study, according to Kuppuswamy's scale, it is found that majority of patients (80%) of atrophic rhinitis belong to low socioeconomic groups. This observation is similar to Jain et al, who reported that atrophic rhinitis is a rare disease in the developed world and quite common in developing country in patient of lower socioeconomic groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…28 In a study by Mishra et al, maximum number of cases was in the age group 21-30 years (40%). 27 The present observations also correlate with the study of Shreedharan et al, and Jain et al 29,30 In the present study, according to Kuppuswamy's scale, it is found that majority of patients (80%) of atrophic rhinitis belong to low socioeconomic groups. This observation is similar to Jain et al, who reported that atrophic rhinitis is a rare disease in the developed world and quite common in developing country in patient of lower socioeconomic groups.…”
Section: Discussionsupporting
confidence: 92%
“…6,26 Mishra et al in their study observed slightly higher incidence in females with male to female ratio of 1:1.5. 27 Atrophic rhinitis is more predominant in females is a well-established fact.…”
Section: Discussionmentioning
confidence: 99%